A challenge in antibiotic stewardship: detection of vancomycin-variable Enterococcus faecium (VVE) in human clinical and commensal samples (2009-2022) - Almeida-Santos, Ana C.; Tedim, Ana P.; Duarte, Bárbara; Silva, Luís M.; Teixeira, Júlio; Castro, Ana P.; Novais, Carla; Peixe, Luísa; Freitas, Ana R. (Scientific Letters, 2024)
Background: Vancomycin-variable-enterococci (VVE) are vanA+ enterococci expressing a vancomycin-susceptible phenotype that can revert to a resistant phenotype (VRE) after vancomycin exposure. Objective: We aimed to screen and characterize VVE in a large collection of Enterococcus faecium (Efm) [1]. Methods: We performed a vanA-PCR screening on an extensive Efm collection (2009-2022), including hospital (n=255) and healthy-human (n=161) isolates, followed by disk-diffusion susceptibility testing. Vancomycin MICs (Etest) were performed in vanA+ isolates with a susceptible phenotype. VVE were sequenced (Illumina-MiSeq/Eurofins-Germany) and representatives of each clonal-complex-CT were sequenced by Nanopore (Plasmidsaurus/USA). cgMLST, antimicrobial resistance and plasmid-replicases (rep;Resfinder/PlasmidFinder-CGE-tools) were evaluated. vanA-transposons and plasmids were characterized and compared to references using Geneious-Prime tools, alongside NCBI blastn/blastx. Results: We identified seven VVE (7/416; 2%), six causing infections (3-urine, 1-pus, 1-blood from 2009 and 1-tissue from 2011) and one healthy-human (2022), indicating daily contact with non-treated water and no hospitalization in the previous 12-months. All VVE were vancomycin susceptible (MIC:1.5-4mg/ml), resistant to ampicillin, erythromycin, ciprofloxacin and identified as ST78: five CT230 (4-clinical;1-commensal) and two clinical CT330. Hybrid assemblies of two clinical isolates, CT230 and CT330, showed a homologous Tn1546 structure with 18,211bp (vanH-vanA-∆vanX-IS1216-vanY-vanZ-other_genes-IS1216-∆tnpA-tnpB-vanR-∆vanS) flanked by IS1216. The presence of ∆vanX and ∆vanS by IS1216-insertions might explain the lack of resistant phenotype. The healthy-human isolate apparently carries an identical Tn1546 (nanopore-sequencing is ongoing). Closed genomes carried two different plasmids with Tn1546. One is a mosaic plasmid (~150kb) presenting Inc18-like-rep_pRE25, Rep1 (rep_pTT39_p3) and Rep3 (∆rep_pVRE1-VanA). The other (~107kb) carried a Rep3-like (rep_pZY2). No homologous plasmids have been described. The healthy volunteer isolate had similar rep content to hospital isolates, possibly indicating plasmid similarities or recombined plasmids. Conclusions: We firstly report identical strains and Tn1546-VVE platforms in human clinical and commensal samples across distant years. This indicates potential colonization leading to VVE selection upon hospital admission and/or antibiotic administration. Continuous surveillance of VVE is crucial for optimizing antibiotic stewardship and ensure effective treatments.